Threshold friction velocities influenced by standing crop residue in the inland Pacific Northwest, USA. (17th April 2020) - Pi, Huawei; Huggins, David R.; Sharratt, Brenton
Abstract: Crop residue is an important factor affecting soil wind erosion. Few studies have tested the effects of crop residue on threshold friction velocities (U*t) which not only controls the initiation of wind erosion events but also the frequency and intensity of erosion events and thus the rate of land degradation. This study measured the threshold friction velocity (U*t) and aerodynamic roughness length ( Z 0 ) in the presence of winter wheat ( Triticum aestivum L.), canola ( Brassica napus L.), and garbanzo ( Cicer arietinum ) standing residue arrays to identify the sheltering capability against wind erosion of these different vegetation patterns. The influence of crop residue density and lateral cover (total roughness frontal area to soil surface area) on U*t and Z 0 was tested in a wind‐tunnel. The results indicated U*t increased linearly with residue density for the three residue types and a similar trend was found for Z 0 . However, U*t and Z 0 varied among crop residue types at the same residue density or frontal area index (λ). Based on the slope of regression analysis, U*t and Z 0 of garbanzo were 40 and 25% higher than winter wheat and 43 and 119% higher than canola. This study suggested that crop residue type is important in determining U*t and Z 0 when modeling wind erosion.